(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The notion of this research is to discover official ethics on administration service in the office of Civil Service Agency and Human Resource Development in Bone District. This research was descriptive qualitative method that used type of phenomenology research, and technique of data analysis used includes data reduction, data presentation, and conclusion drawing. The data in this research taken from seven informants. Technique of data collecting was deep interview, direct observation, and take documentation. The result of this research showed that the official ethics on administration services has been running consist of four aspects, namely Equality, The value of the equation that is run is good, Equity, The maximum applied justice is seen. Loyalty, Employed loyalty is shown direcly by looking at the performance and obeying the existing rules. Responsibility , in carrying out the service has been responsible but in terms of discipline, especially discipline when there are still many employess who do not attend on time and make Government employees waiting service.